Acute kidney injury in patients treated with aminoglycosides (Actualizaciones en Sida e Infectología, 2020)
The risk of developing renal failure associated with the use of aminoglycosides is often a limitation for its use in many health professionals. The objective of this study was to know the frequency of renal failure in patients treated with aminoglycosides and the possible factors associated with their appearance.Materials and methods: descriptive, longitudinal and prospective study. Patients who received aminoglycosides for at least 72 hours were included. Basal creatinine was measured and every 48 hours during the antibiotic treatment and after 7 days or more of its suspension. Acute renal failure was defined as an increase in creatinine of 0.3 mg/dl compared to baseline.Results: data from 107 patients were analyzed, and the frequency of renal failure was 10.3%, being 5.8% during the treatment with aminoglycoside and 4.5% after its suspension. The patients who developed renal failure had higher doses of aminoglycoside respect to the group that did not present this event, being this difference statistically significant.Conclusions: the frequency of renal failure in patients treated with aminoglycosides was within the ranges described in the literature and the majority of patients had complete recovery of renal function. We believe that renal failure does not represent a clinically significant adverse effect if aminoglycosides are used with adequate precautions. This, added to their good clinical results and low impact on bacterial ecology, makes them very used antibiotics today in our hospital.
Keywords: aminoglycosides; acute kidney injury; anti-bacterial agents